Sense of coherence and physical health–related quality of life in Italian chronic patients: the mediating role of the mental component - Maura Galletta; Manuela Cherchi; Alice Cocco; Giacomo Lai; Valentina Manca; Martina Pau; Federica Tatti; Giorgia Zambon; Simona Deidda; Pierangelo Origa; Elena Massa; Efisio Cossu; et al. (BMJ Open)
Objective To examine the relationship between sense of coherence (SOC) and physical health–related quality of life in patients with chronic illnesses by focusing on the mediating role of the mental component of quality of life.Design Cross-sectional survey design.Setting Secondary care; three departments of an Italian university hospital.Methods The participants (n=209) in the study were adult (≥18 years) outpatients with a chronic pathology (eg, diabetes, thyroid disorders or cancer) at any phase in the care trajectory (eg, pre-treatment, undergoing treatment, follow-up care). They agreed to participate in the study after providing their informed consent. Data were collected using a structured self-reporting questionnaire. Data analysis was carried out using SPSS, and mediation analysis was performed via PROCESS macro.Results The SOC score of the study sample was equivalent to that of the general population (mean difference=−2.50, 95% CI −4.57 to 0.00). Correlation analysis showed that SOC was mainly correlated to the mental component (MCS) (r=0.51, p<0.01) of quality of life and then to the physical component (PCS) (r=0.35, p<0.01). Mediation analysis showed that SOC was directly related to MCS (p<0.001, 95% CI 0.62 to 0.99) but not to PCS (p=0.42, 95% CI −0.27 to 0.12). In turn, MCS was directly related to PCS (p<0.001, 95% CI 0.76 to 1.01). The indirect effect of SOC on PCS through MCS was significant (0.71, p<0.001, bootstrap 95% CI 0.54 to 0.91), thus supporting the mediating role of the mental component of quality of life.Conclusion The indirect effect suggests that SOC is a marker of quality of life, especially of the mental component. The findings show that SOC is a psychological process that impacts patients’ mental health status, which in turn affects physical health. Better knowledge of a person’s SOC and how it affects his/her quality of life may help to plan tailoring interventions to strengthen SOC and improve health-related quality of life.